Drug delivery device for the inner ear: ultra-sharp fully metallic microneedles - Aksit, Aykut; Rastogi, Shruti; Nadal, Maria L.; Parker, Amber M.; Lalwani, Anil K.; West, Alan C.; Kysar, Jeffrey W. (Drug delivery and translational research, 2021)
Drug delivery into the inner ear is a significant challenge due to its inaccessibility as a fluid-filled cavity within the temporal bone of the skull. The round window membrane (RWM) is the only delivery portal from the middle ear to the inner ear that does not require perforation of bone. Recent advances in microneedle fabrication enable the RWM to be perforated safely with polymeric microneedles as a means to enhance the rate of drug delivery from the middle ear to the inner ear. However, the polymeric material is not biocompatible and also lacks the strength of other materials. Herein we describe the design and development of gold-coated metallic microneedles suitable for RWM perforation. When developing microneedle technology for drug delivery, we considered three important general attributes: (1) high strength and ductility material, (2) high accuracy and precision of fabrication, and (3) broad design freedom. We developed a hybrid additive manufacturing method using two-photon lithography and electrochemical deposition to fabricate ultra-sharp gold-coated copper microneedles with these attributes. We refer to the microneedle fabrication methodology as two-photon templated electrodeposition (2PTE). We demonstrate the use of these microneedles by inducing a perforation with a minimal degree of trauma in a guinea pig RWM while the microneedle itself remains undamaged. Thus, this microneedle has the potential literally of opening the RWM for enhanced drug delivery into the inner ear. Finally, the 2PTE methodology can be applied to many different classes of microneedles for other drug delivery purposes as well the fabrication of small scale structures and devices for non-medical applications. Graphical Abstract Fully metallic ultra-sharp microneedle mounted at end of a 24-gauge stainless steel blunt syringe needle tip: (left) Size of microneedle shown relative to date stamp on U.S. one-cent coin; (right) Perforation through guinea pig round window membrane introduced with microneedle.